Perencanaan Biaya Pemeliharaan Dan Perawatan Bangunan Gedung Rumah Sakit Universitas Riau Berdasarkan Permen NO/24/PRT/M/2008 - Malitha, Reonaldho; Iriana, Rian Tri Komara (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The continued development of a state is accompanied by the increase the need for health care facilities in the country. Health care facilities that exist today is the hospital. Thehospital is a health care institution for people with special characteristics that remain able to improve the quality and service more affordable for the people to manifest the health status of the highest. Maintenance of the building is very important and necessary after the building was completed and used. According to the regulation of the Minister of Public Works No. 24/PRT/M/2008 on Guidelines for Maintenance and Building Maintenance, building maintenance aims to be the realization of the building according to the function set andwhich meets the technical requirements: salvation, health, comfort and ease as well as environmental sustainability. This research was conducted by estimated price forecast(Approximate Estimate) that uses the highest unit price of the average per-m2 storey building to building accurate as a guide. Based on the analysis using approximate estimate method, the result is the percentage of damage that is equal to 0.01015%. While the cost of repair needed is Rp. 3,846,924.687. So it can be categorized damage RSUR building is still in the level of minor damage (<35%). As for the cost of maintenance per year is Rp.2,540,631,517.33 which is expected to increase each year.Keyword : maintenance of building, the university hospital in Riau.